PROFIL KEMAMPUAN BERPIKIR REFLEKTIF SISWA MTs NURUL HUDA SUGIO DALAM MENYELESAIKAN SOAL CERITA PADA MATERI POLA BILANGAN DITINJAU DARI LEVEL MOTIVASI BELAJAR - Zunia Fidya Astutik; Arezqi Tunggal Asmana; Zaenal Arifin (INSPIRAMATIKA, 2022)
This study aims to determine the relationship between reflective thinking and students' learning motivation in mathematics. This type of research is descriptive research with a qualitative approach, because it produces written data that is more comprehensive. The subjects of this study were 9 students of class VIII MTs Nurul Huda Sugio in the 2021/2022 academic year. The determination of the subject is based on the results of the student learning motivation questionnaire. The instrument given to the research subjects was in the form of a test consisting of 5 story questions, student learning motivation questionnaires and interviews. The data used are test results, questionnaire results and interview recordings. Based on the data analysis that has been done, the results of this study indicate that there are differences in students' reflective thinking abilities at each level of student motivation in learning mathematics. Results Based on the data analysis, it was obtained that: (1) The profile of students' reflective thinking abilities with learning motivation level obtained an average score of 77; (2) Profile of students' reflective thinking abilities with moderate learning motivation obtained an average score of 31.33; (3) The reflective thinking ability profile of students with low learning motivation obtained an average score of 6.67.